2008
DOI: 10.1192/bjp.bp.106.029280
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of psychiatric disorders in South Africa

Abstract: In comparison with data from other countries, South Africa has a particularly high lifetime prevalence of substance use disorders. These disorders have an early age at onset, providing an important target for the planning of local mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
6
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 19 publications
8
166
6
4
Order By: Relevance
“…This rate is considerably higher than the lifetime prevalence of depression (9.8%) that has been documented in the South African general population. 22 The number of hours worked, the work load, working conditions and public system-related frustrations were ranked as the most important factors that contributed to burnout. This corresponds with existing data, and with current circumstances in primary care settings, where doctors are limited in number, and yet services are needed 24 hours a day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is considerably higher than the lifetime prevalence of depression (9.8%) that has been documented in the South African general population. 22 The number of hours worked, the work load, working conditions and public system-related frustrations were ranked as the most important factors that contributed to burnout. This corresponds with existing data, and with current circumstances in primary care settings, where doctors are limited in number, and yet services are needed 24 hours a day.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the life time prevalence of mood disorders in the general population between 2002 and 2004 was reported to be 9.8%. 22 …”
Section: Introductionmentioning
confidence: 99%
“…African societies differ in their BMI profiles (Puane et al, 2002) and mental health presentation (Stein et al, 2008), which leads to the question whether the associations described elsewhere would hold true for SA samples.…”
Section: Rationalementioning
confidence: 99%
“…However, a recent nationwide study conducted by Tomlinson et al (2009) found that approximately 9.7% of the adult participants were diagnosed with MDD. Also, a recent study conducted by Stein et al (2008) investigated the lifetime prevalence of psychiatric disorders in South Africa and found that 9.8% of the population suffered from MDD.…”
Section: Synthesis and Critical Evaluation Of The Literature Depressimentioning
confidence: 99%